ANALYSIS OF THE IMPLEMENTATION OF PERFORMANCE ASSESSMENT ON THEMATIC LEARNING IN ELEMENTARY SCHOOLS - Wafiqni, Nafia; Marini, Arita; Sari, Putri Ilam (JMIE (Journal of Madrasah Ibtidaiyah Education), 2022)
This research was conducted to obtain an overview of teacher planning, implementation and reporting in the assessment of performance in thematic learning in elementary schools. This reseach uses descriptive qualitative method. The subjects in this strudy were the principal, elementary school coordinator teacher, and teachers grade I – VI. The techniques used in data collection are interviews, observation, and documentation. This study will obtain complete data, namely primary data and secondary data, where primary data is obtained through observations and interviews, while secondary data is obtained through documents, photographs and videos related to performance work. Data were analyzed through steps of data reduction, data presentation, and conclusion concluded. The results of this study show three conclusions. First, planning decides the performance assessment to complete the objectives to be achieved, chooses activities that are suitable for students, determines assessment criteria and compiles a performance rubric. Second, approve the performance assessment, complete the discussion of the availability of tools and materials, provide and submit the rubric of the performance, conduct question and answer and discussion about the rubric, monitor the process of carrying out the performance tasks, conduct research according to the rubric, improve it and improve it. Third, reporting the performance assessment is presented in the form of numbers and descriptions that are delivered to students, fellow teachers, school management teams and participants at PTC (Parent Teacher Conference). Performance appraisal encourages comprehensive, teachers apply performance appraisal in applying the knowledge and attitudes that students relate to performance skills. Carrying out performance tasks is hampered by time, solutions that can be done provide students with understanding material before carrying out performance tasks.